Evaluation of the regulation changes in medical waste management in Turkey - Eker, Hasan Huseyin; Bilgili, Mehmet Sinan; Sekman, Elif; Top, Selin (SAGE PUBLICATIONS LTD, 2010)
In this study, a survey containing 28 questions concerning general information about the healthcare services, waste collection, training, waste quantities, storage and general evaluation was applied to 311 healthcare services. The response rate was 82%, which was considered acceptable for the evaluation of the results. The separate collection of medical waste and sharps was completely achieved in all of the healthcare services participating in the survey and 82.6% of the healthcare services used containers for separate collection of medical waste. Only 5% of the containers used for waste collection and temporary storage were inappropriate for collecting medical waste. Almost 33% of healthcare services organized courses monthly, 40% quarterly and 20% at least twice a year. A total of 88% of the hospitals have temporary storage depots for medical waste and all of these depots complied with the Medical Waste Control Regulation. The results of this study showed that the medical waste generation rate was 2.35 kg bed(-1) day(-1). The amount of liquid waste and sharps was determined for the first time in Turkey. The rate of separate collection for recyclables increased to 94%, having been 83% in 2006. The results indicate that in the period 2006-2009, the healthcare services conformed completely to the Medical Waste Control Regulation as it applied. Any deficiencies observed will be satisfied by precautionary actions that will be taken by hospital managers and local administrations.
Keywords: Medical waste; medical waste management; regulations; healthcare services; Engineering; Environmental Sciences & Ecology